World Development Report 2000/2001 : Attacking Poverty - World Bank (New York Oxford University Press, 2001)
At the start of each decade the "World Development Report" focuses on poverty reduction. This 23rd edition of the annual report proposes means of reducing poverty in the 21st-century using the diverse experiences of poverty reduction during the last 15 years.
Include Graph, Illustration, Bibliography, Note and Table
Keywords: Poverty -- Economic development -- Poverty--International cooperation -- Developing countries -- Poor -- Economic history -- Economic indicators